Makhṭūṭat Kinanti [Tutur Teu Kacatur Batur]: Taṣawwuf al-‘ālam al-Sūndāwī ‘inda al-Ḥāj Ḥasan Muṣṭafà (1852-1930) - Rohmana, Jajang A. (Studia Islamika, 2013)
Although the influence of Sundanese interpretations of Islam is not clearly evident in Indonesia’s Islamic networks, these local interpretations have played a crucial role in the indigenization of Islam in the region. This article analyses Haji Hasan Mustapa’s dangding manuscript on Sundanese expressions of Sufism in the 19th century. Mustapa’s teachings on Sundanese dangding sufism suggests efforts to harmonize waḥdat al-wujūd teachings with Sundanese tradition. Mustapa’s work harmoniously integrates mystical Islam teachings and practices with Sundanese traditions. For example, the flora and fauna imagery and metaphors associated with Sundanese culture often adorns his metrical verses (dangding). Tadpoles, angklung and various kinds of bamboo such as awi, haur and iwung are also used in the context of his mystical and spiritual quest in waḥdat al-wujūd.DOI: 10.15408/sdi.v20i2.390